SIFAT FISIS DAN MEKANIS PURUN BAJANG SEBAGAI SUBSTITUSI PURUN DANAU DAN PURUN TIKUS - Dwi Harsono (Kementerian Perindustrian, 2013)
The problem faced by purun craftsmen is the reduced of purun raw material which commonly used such as purun danau and purun tikus. Hence it tends to utilized purun bajang which lesser known but potential used as a raw material purun craft. The research aims to obtain the information on the physical and mechanical properties of purun bajang compared with purun tikus and purun danau as substituted of purun tikus and purun danau.The research conclude that purun bajang’s performance is almost same as another commercial purun in terms colour and impression touch, but purun bajang relative slippery than purun tikus and purun danu. Purun bajang can be used as material substitution of commercialized purun tikus and purun danau, but it is noteworthy because of the tensile strength which it have very low tensile strength. Purun bajang can be used as woven material after drying process without any pulverization because it cause increasingly fragile tensile strength.Keywords: purun, physical properties, mechanical properties